Protein Serine/Threonine Phosphatase Type 2C of Leishmania mexicana - Escalona-Montaño, Alma Reyna; Zuñiga-Fabián, Mariana; Cabrera, Nallely; Mondragón-Flores, Ricardo; Gómez-Sandoval, Jenny Nancy; Rojas-Bernabé, Araceli; González-Canto, Augusto; Gutiérrez-Kobeh, Laila; Pérez-Montfort, Ruy; Becker, Ingeborg; Aguirre-García, Maria Magdalena (Frontiers in Cellular and Infection Microbiology, 2021)
Protein phosphorylation and dephosphorylation are increasingly recognized as important processes for regulating multiple physiological mechanisms. Phosphorylation is carried out by protein kinases and dephosphorylation by protein phosphatases. Phosphoprotein phosphatases (PPPs), one of three families of protein serine/threonine phosphatases, have great structural diversity and are involved in regulating many cell functions. PP2C, a type of PPP, is found in Leishmania, a dimorphic protozoan parasite and the causal agent of leishmaniasis. The aim of this study was to clone, purify, biochemically characterize and quantify the expression of PP2C in Leishmania mexicana (LmxPP2C). Recombinant LmxPP2C dephosphorylated a specific threonine (with optimal activity at pH 8) in the presence of the manganese divalent cation (Mn+2). LmxPP2C activity was inhibited by sanguinarine (a specific inhibitor) but was unaffected by protein tyrosine phosphatase inhibitors. Western blot analysis indicated that anti-LmxPP2C antibodies recognized a molecule of 45.2 kDa. Transmission electron microscopy with immunodetection localized LmxPP2C in the flagellar pocket and flagellum of promastigotes but showed poor staining in amastigotes. Interestingly, LmxPP2C belongs to the ortholog group OG6_142542, which contains only protozoa of the family Trypanosomatidae. This suggests a specific function of the enzyme in the flagellar pocket of these microorganisms.